Evaluation of Distance and Face-to-Face Anatomy Education From the Perspective of Students During the COVID-19 Pandemic Period - Aksu, Feyza; Akkoc, Ramazan Fazil; Aras, Onur; Ogeturk, Murat (Soc Chilena Anatomia, 2023)
During the COVID-19 pandemic, a questionnaire was administered to the students who took anatomy courses through distance education in the Faculties of Medicine and Dentistry. Through the questionnaire, the aim was to figure out whether the infrastructure of Firat University was ready and adequate for distance education, how efficient the distance theoretical and practical anatomy classes were, and in what proportions the students would prefer to take face-to-face and distance anatomy classes when the pandemic is over. A questionnaire of 35 questions was applied to 555 students studying at the Medicine and Dentistry Faculties of Firat University. The students widely accepted the opinion that Firat University successfully implemented the distance education system, and distance education offered the opportunity to receive the lessons repeatedly regardless of time and place. In addition, it has been determined as a common opinion that anatomy classes given via distance education were equally beneficial as face-to-face education in terms of duration, content, and efficiency. Despite these advantages, the lack of face-to-face interaction and weak information permanence were reported as the negative aspects of distance education. The students emphasized that applied anatomy classes and especially cadaver studies should be conducted face to face. Anatomy education is quite substantial in the acquisition and development of professional skills. It is considered that distance anatomy education will be inadequate to provide this gain. The high demand for face-to-face practical classes by students also backs this up.
Evaluación de la Educación Anatomía a Distancia y Presencial desde la Perspectiva de los Estudiantes Durante el Período de Pandemia del COVID-19
Keywords: Anatomy; COVID-19 pandemic; Distance education; Face to face education